The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7554/elife.54257
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-4 in bone marrow driven dysregulated angiogenesis and age-related macular degeneration

Abstract: Age-associated sterile inflammation can cause dysregulated choroidal neovascularization (CNV) as age-related macular degeneration (AMD). Intraocular fluid screening of 234 AMD patients identified high levels of IL-4. The purpose of this study was to determine the functional role of IL-4 in CNV formation using murine CNV model. Our results indicate that the IL-4/IL-4 receptors (IL4Rs) controlled tube formation and global proangiogenic responses of bone marrow cells. CCR2+ bone marrow cells were recruited to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…These PSNs potentially release CCL2 that signals to monocytes and dendritic cells, as well as IL18 that signals back to basophils (Figure 4B, C and S6). Indeed, IL4 has been shown to induce CCL2 release from bone-marrow derived endothelial progenitor cells (Baba et al, 2020), and similar mechanism may exist in PSNs.…”
Section: Psn Sensing and Signaling Inflammationmentioning
confidence: 94%
“…These PSNs potentially release CCL2 that signals to monocytes and dendritic cells, as well as IL18 that signals back to basophils (Figure 4B, C and S6). Indeed, IL4 has been shown to induce CCL2 release from bone-marrow derived endothelial progenitor cells (Baba et al, 2020), and similar mechanism may exist in PSNs.…”
Section: Psn Sensing and Signaling Inflammationmentioning
confidence: 94%
“…This study concluded that, although VEGF-A was upregulated, pulmonary angiogenesis was diminished in the absence of IL-4, confounding the role of IL-4 in hypoxia-induced angiogenesis from earlier reports [32]. Later studies have also indicated that IL-4 promotes angiogenesis via direct effects on endothelial cells [33]. One such study focused on age-related macular degeneration and concluded that IL-4 promoted choroidal neovascularization both by directly stimulating tube formation in endothelial progenitor cells and by inducing vasculogenesis through bone marrow-derived endothelial progenitor cells [33].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 85%
“…Later studies have also indicated that IL-4 promotes angiogenesis via direct effects on endothelial cells [33]. One such study focused on age-related macular degeneration and concluded that IL-4 promoted choroidal neovascularization both by directly stimulating tube formation in endothelial progenitor cells and by inducing vasculogenesis through bone marrow-derived endothelial progenitor cells [33]. Another study in an atopic dermatitis model showed that IL-4 dysregulates the expression of microRNAs involved in angiogenesis which may contribute to the excessive angiogenesis seen in disease pathogenesis [34].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…EPCs capable of contributing to capillary formation can be derived from bone marrow cells [ 61 , [63] , [64] , [65] , [66] ]. Baba aet al reported that bone marrow-derived cells can differentiate into ECs within the CNV lesion [67] . Feng aet al recently reported [68] that there is no evidence for erythromyeloid progenitor-derived vascular endothelial cells in multiple organs during development.…”
Section: Discussionmentioning
confidence: 99%